2001
DOI: 10.1152/jn.2001.85.1.414
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Anoxic Depolarization During Ischemia-Like Conditions in the Mouse Hemi-Brain Slice

Abstract: Focal ischemia evokes a sudden loss of membrane potential in neurons and glia of the ischemic core termed the anoxic depolarization (AD). In metabolically compromised regions with partial blood flow, peri-infarct depolarizations (PIDs) further drain energy reserves, promoting acute and delayed neuronal damage. Visualizing and quantifying the AD and PIDs and their acute deleterious effects are difficult in the intact animal. In the present study, we imaged intrinsic optical signals to measure changes in light t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
85
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 51 publications
12
85
1
Order By: Relevance
“…To analyze the effect of blocking GABA receptors on the swelling that occurred at the time of the AD, we used the fact that in submerged slices swelling leads to less scattering of light passing through the slice and so increases the intensity of transmitted light (Kreisman et al, 1995;Joshi and Andrew, 2001). This is because intracellular organelles scatter light and reduce the transmitted light, but when cells swell, the organelles are diluted, reducing scattering and increasing transmittance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the effect of blocking GABA receptors on the swelling that occurred at the time of the AD, we used the fact that in submerged slices swelling leads to less scattering of light passing through the slice and so increases the intensity of transmitted light (Kreisman et al, 1995;Joshi and Andrew, 2001). This is because intracellular organelles scatter light and reduce the transmitted light, but when cells swell, the organelles are diluted, reducing scattering and increasing transmittance.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate this, we used the fact that cell swelling leads to a decrease of light scattering and an increase of light transmittance through the slice (Kreisman et al, 1995;Joshi and Andrew, 2001), as schematized in Figure 7A. Figure 7B shows a specimen record of light transmittance during application of normal ischemic solution.…”
Section: Blocking Gaba a Receptors Increases The Admentioning
confidence: 99%
“…In addition, we have recently reported that certain sigma-one receptor ( 1 R) ligands are effective in preventing the propagating wave of anoxic depolarization (AD) (Anderson et al 2000). This wave arises under simulated ischemia and, if unchallenged, leaves cells damaged in its wake (Obeidat and Andrew 1998;Jarvis et al 2001;Joshi and Andrew 2001). Similarities between normoxic and hypoxic SD have been noted (Aitken et al 1998).…”
Section: Introductionmentioning
confidence: 95%
“…The rate of SD propagation is predicted to increase when (1) extracellular K + removal is hampered, (2) the extracellular space is smaller (cell swelling), and (3) extracellular K + and/or glutamate concentrations are increased [73]. In line with the predictions, hypoxic SDs tended to propagate approximately 1 mm/min more rapidly than normoxic SDs as observed in brain slices [74,75]. These data in combination with our findings suggest that the tissue at the SD focus may be more hypoxic than in the surrounding area.…”
Section: 3the Focal Area Of Spreading Depolarizationssupporting
confidence: 61%